Clinical Factors Related to Noncompletion of - Clinical Factors Related to Noncompletion of (Blackwell Synergy, 2000)
This study identified clinical factors related to noncompletion of root canal therapy (RCT) among patients in a dental health maintenance organization (HMO) based in Portland, OR.